United as One - Book 7 - Lore, Pittacus (New York : Harper, an imprint of HarperCollins, 2017)
The Mogadorians have invaded Earth. The Garde are all that stand in the way, but they'll need an army of their own to win this fight. They've teamed up with the US military, but it might not be enough. The Garde need reinforcements, and they've found them in the most unexpected place. Teenagers from across the globe, like John Smith's best friend, Sam, have developed abilities. But after all the Mogadorians have taken from John--his home, his family, his friends, and the person he loves most--he might not want to put any more lives in danger. He's got nothing left to lose, and he's just discovered he has been given an incredible new Legacy. Now he can turn himself into the ultimate weapon. So will he risk his life to save the world, or will he realize that power in numbers will save us all?
Keywords: Extraterrestrial beings -- Juvenile fiction; Human-alien encounters -- Juvenile fiction; Friendship -- Juvenile fiction; Best friends -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Extraterrestrial beings -- Fiction; Science fiction; Best friends; Extraterrestrial beings; friendship; Human-alien encounters; Imaginary wars and battles; Extraterrestrial beings -- Fiction; Human-alien encounters -- Fiction; Young adult fiction; Fiction; Juvenile works; Science fiction; Young adult works; Science fiction